Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3947/ic.2016.48.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Antibiotic-Resistant Gram-Negative Bacterial Infections in Febrile Neutropenic Children

Abstract: BackgroundThe incidence of bacteremia caused by Gram-negative bacteria has increased recently in febrile neutropenic patients with the increase of antibiotic-resistant Gram-negative bacterial infections. This study aimed to identify the distribution of causative bacteria and the proportion of antibiotic-resistant bacteria in bacteremia diagnosed in febrile neutropenic children.Materials and MethodsThe medical records of febrile neutropenic children diagnosed with bacteremia between 2010 and 2014 were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 22 publications
2
34
2
4
Order By: Relevance
“…In a study conducted in Turkey, it was reported that febrile neutropenia attacks developed most commonly during the consolidation treatment in patients with pediatric leukemia treated with the BFM protocol (29). In the study conducted by Lee et al (38), it was reported that febrile neutropenia most commonly developed after the consolidation period. In our study, febrile neutropenia attacks developed most commonly in the reinduction period.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Turkey, it was reported that febrile neutropenia attacks developed most commonly during the consolidation treatment in patients with pediatric leukemia treated with the BFM protocol (29). In the study conducted by Lee et al (38), it was reported that febrile neutropenia most commonly developed after the consolidation period. In our study, febrile neutropenia attacks developed most commonly in the reinduction period.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de que generalmente la fiebre en estos niños es secundaria a una condición infecciosa benigna (por ejemplo, una virosis), hasta 20% pueden tener una infección bacteriana grave [16][17][18] (Tabla 1). Uno de los aspectos más importantes para el manejo del paciente es la búsqueda de la "puerta de entrada" de agentes infecciosos al torrente sanguíneo.…”
Section: Búsqueda De Foco Infecciosounclassified
“…Uno de los aspectos más importantes para el manejo del paciente es la búsqueda de la "puerta de entrada" de agentes infecciosos al torrente sanguíneo. Para ponerlo en perspectiva, esto es el doble de riesgo que tienen los neonatos febriles [16][17][18] . Debido a que la reacción inflamatoria del paciente con neutropenia febril es escasa o está ausente, no focaliza adecuadamente las infecciones 4 .…”
Section: Búsqueda De Foco Infecciosounclassified
See 1 more Smart Citation
“…All the positive evidence thus lies on the older trials, which 1) Included mainly bacterial infections 2) Precede modern antibiotics like third-generation cephalosporins and carbapenems 3) Precede the era of growth factors that may shorten the duration of neutropenia and 3) Precede the use of new antifungals like voriconazole, posaconazole or echinocandins. Of particular interest, the control groups in the early positive controlled trials documented the mortality of gram-negative bacteremia to be 70–100%, which seem to be much worse than current practice: the mortality of gram-negative bacteremia in neutropenic patients currently reported varies between 5% for susceptible bacteria and 20% for resistant bacteria [36,37]. …”
Section: Gtx For Treatment Of Infection: Review Of Recent Studies (Pomentioning
confidence: 99%